A patient with penile metastasis secondary to small cell lung cancer successfully treated with PD-1 inhibitors and chemotherapy: a case report and literature review - Zhang, Kai-cong; Li, Wei-jun; Xu, Hui-xin; Liang, Hui-min; Yang, Qiong (Frontiers in Oncology, 2025)
BackgroundPenile metastasis is an uncommon condition, with most primary malignancies originating in the abdominal cavity and pelvis. There have been very few reported cases originating from lung cancer, most of squamous cell carcinoma without small cell lung cancer.MethodsWe presented a case of penile metastasis secondary to small cell lung cancer, along with a review of relevant literature from the CNKI database.ResultsA 73-year-old male presented with a one-month history of palpable swelling in the penis without any chest symptoms. Beside penile lesion, PET/CT imaging also revealed a lesion in the left lobe of the lung, as well as multiple enlarged lymph nodes in the left hilum, mediastinum, and left supraclavicular fossa. Fiberoptic biopsy confirmed small cell lung cancer for the pulmonary mass, while biopsies of the penile mass confirmed metastatic small cell carcinoma. The patient received first-line treatment of 6 cycles of PD-1 inhibitor (Toripalimab) combined with etoposide and cisplatin, achieving a partial response (PR). Subsequently, second-line therapy of etoposide and cisplatin regimen and later-line therapies of Irinotecan followed by Anlotinib were administered. The overall survival was approximately 2 years.ConclusionPenile metastasis from small cell lung cancer is extremely rare. Treatment strategies based on guidelines for small cell lung cancer had been proven effective approaches.